Soda-anthraquinone, kraft and organosolv pulping of holm oak trimmings. (Bioresource technology, 2006)
The operating conditions for an organosolv (ethyleneglycol) and two alkaline (soda-anthraquinone and kraft) processes for obtaining cellulose pulp and paper from holm oak (Quercus ilex) wood trimmings were optimized. A range of variation for each process variable (viz. temperature, cooking time and soda or ethyleneglycol concentration) was established and a central composite experimental design involving three independent variables at three different variation levels was applied. The results obtained with the three cooking processes used were compared and those provided by the kraft process were found to be the best. Thus, the tensile index values it provided (5.9-16.3 N m/g) were 23.7% and 41.5% better than those obtained with the soda-AQ and ethyleneglycol processes, respectively. Also, the kraft process provided the best burst index, brightness and kappa number values. Based on the optimum working ranges, the temperature and cooking time were the variables resulting in the most and least marked changes, respectively, in pulp properties.